THEORETICAL FOUNDATIONS OF UZBEKISTAN'S FLEXIBILITY TO INTERNATIONAL FINANCIAL AND ECONOMIC RATINGS (World Economics and Finance Bulletin, 2024)
Today, special importance is attached to the need to systematically analyze the level of socio-economic and political-legal development of the country, to ensure that the implemented fundamental changes serve the purpose of improving the country's position in international rankings and indexes, and to improve the control and law-making functions of the parliament. In this regard, systematic work on ratings is being carried out in our country, and about 10 normative legal documents have been adopted in this field in recent years. However, taking into account the importance of this direction, it was noted that it is necessary to significantly improve the activities of the parliament aimed at these goals.
Keywords: Socio-Economic; Political-Legal Development; parliament